Otoritas Pemerintah Dalam Penetapan Awal Ramadhan Dan Hari Raya: Analisis Kaidah Al-Ijtihadu Laa Yunqadhu Bil Ijtihad - Syahida Asia Almuqarramah; Mustabesyirah H; Nur Azizah; Fitria Yusuf (CV. SINAR HOWUHOWU, 2026)
This study aims to examine the definition of ijtihad, the fundamental principle of al-ijtihadu la yunqadu bil-ijtihad, and its application in addressing government decisions regarding the determination of the beginning of Ramadan and Eid using the new MABIMS criteria. The results indicate that ijtihad is an elemental and vital instrument in constructing Islamic jurisprudence (fiqh) to ensure its continued relevance in addressing contemporary challenges. In the modern context, the implementation of the new MABIMS criteria—which updates the minimal hilal (crescent moon) visibility altitude from 2 degrees to 3 degrees—represents a governmental ijtihad enacted for the public interest (maslahah). This step serves as a tangible manifestation of the al-ijtihadu la yunqadu bil-ijtihad maxim, wherein the new ijtihad adopted by the government is pursued for a greater collective benefit without invalidating the legality of prior ijtihad or past rulings.